Guarantees of Protection of Animals and Birds in Criminal Law (Georgian reality) - Giorgi Latsabidze (European Scientific Journal, ESJ, 2023)
Animals and birds play an important role in human life, and the creation of a perfect legal framework for the protection of their rights has been discussed many times.To date, Article 259 of the Criminal Code of Georgia has undergone several legislative changes, none of which were fundamental, and the main changes were about to increased the  sentences. As can be seen from practice, article 259 of the Criminal Code of Georgia cannot fully describethe list of actions for  which a person can be  punished and a person can commit such an action towards an animal and/or bird that his action cannot be punished by criminal law.Article 259 of the Criminal Law Code of Georgia protects animals from torture, ill- treatment, and other forms of violence and article 104 of the Code of Administrative Offenses deals with improper treatment. Despite the existence of these articles, it is difficult to distinguish whether a person's action is an administrative law violation or criminal liability. Also, the legislator uses such terms that make it even more difficult to solve the issue.